VD_FINDINFO HC / 2024 / 362 vom 9. Juli 2024 - VD Tribunal cantonal (2024)
DROIT DU TRAVAIL, RÉSILIATION EN TEMPS INOPPORTUN, GROSSESSE, DEMEURE DU CRÉANCIER | 101 CO, 321a CO, 324 CO, 336c al. 2 CO, 55 CO